IDENTIFICAÇÃO DO BACTERIOMA DE Stomoxys calcitrans E POTENCIAL IMPACTO ECONÔMICO À PECUÁRIA DOS SURTOS ASSOCIADOS AO SETOR SUCROENERGÉTICO - Eronides Marques de Souza (2022)
Stable fly (Stomoxys calcitrans) is an insect that parasitizes several groups of animals, including humans. In recent decades, outbreaks of this fly have been recorded in several regions of the country, especially in cities of Mato Grosso do Sul, Mato Grosso, Goiás, Minas Gerais and São Paulo. These areas are characterized by the expansion of the sugar-alcohol industry, which may justify the presence of the outbreaks, since, with the prohibition of pre-harvest burning, the sugarcane straw starded to accumulate in plantations and moistened with vinasse, making it an environment conducive to larval development. As it is a hematophagous insect and causes painful bites, S. calcitrans causes economic losses in cattle, interfering in the health of the animal and, consequently, reducing the production. Some researches indicate the importance of S. calcitrans as a possible mechanical and biological vector of several pathogens, but few studies have been carried out involving field situations, as well as the identification and isolation of microorganisms in wild flies. The objectives of the present study were to estimate the economic impact resulting from the outbreaks of this fly in cattle, as well as the annual losses to brazilian sugar-energy industry; and at the same time, with the aid of metagenomics and bioinformatics, to identify the bacteriome present in DNA extracted from stable flies. The potential annual economic impact of the outbreaks, associated with the sugar-energyl industry, was estimated at R$ 1,065 billion (US$ 205,38 million) for Brazilian cattle. While the estimated potential damage to the sugar-energy industries accumulated values of R$ 43,743 million (US$ 8,428 million) per year. The final amount of financial losses to the brazilian cattle and bioenergy sectors was R$ 1.109.667.348,27 (US$ 213.808.737,62). Through metagenome analysis, a vast diversity of bacteria was identified, highlighting four phyla Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria. The bacteria of the Proteobacteria phylum showed the highest relative frequency in the three groups of stable fly DNA samples, but the samples from Patio II (Embrapa) showed the greatest variety of bacterial phyla. Future studies will be necessary for a better understanding of the range of bacteria carried by S. calcitrans, as well as the need for a better understanding of the dynamics related to the dispersion of the pathogens of importance in cattle farming. Antecipating scenarios can be the starting point for the development of preventive processes linked to the stable fly in the entire structure that involves sugar-energy activities and cattle raising systems in its vicinity. Keywords: Bioinformatics, DNA, Losses, Metagenomics, Stable fly.